2011
DOI: 10.1136/annrheumdis-2011-200092
|View full text |Cite|
|
Sign up to set email alerts
|

Statin use is associated with reduced incidence and progression of knee osteoarthritis in the Rotterdam study

Abstract: Background Osteoarthritis is the most frequent chronic joint disease causing pain and disability. Besides biomechanical mechanisms, the pathogenesis of osteoarthritis may involve infl ammation, vascular alterations and dysregulation of lipid metabolism. As statins are able to modulate many of these processes, this study examines whether statin use is associated with a decreased incidence and/or progression of osteoarthritis. Methods Participants in a prospective populationbased cohort study aged 55 years and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
116
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 128 publications
(122 citation statements)
references
References 40 publications
(49 reference statements)
4
116
2
Order By: Relevance
“…Adding to our prior analyses, however, is that (1) among persons without arthritis, statin use in the setting of low vitamin D status demonstrated an even higher odds for risk of musculoskeletal pain than found in our main models, and (2) among those with arthritis, statin use in the setting of 25(OH)D ≥15ng/mL was associated with significantly lower odds for risk of musculoskeletal pain. Regarding the second finding, other studies have reported similar observations regarding a possible protective effect of statin on reducing the risk or progression of arthritis [13,14]. However, vitamin D supplementation, on its own, was not found to improve symptoms or prevent progression of osteoarthritis [15].…”
Section: Discussionsupporting
confidence: 56%
“…Adding to our prior analyses, however, is that (1) among persons without arthritis, statin use in the setting of low vitamin D status demonstrated an even higher odds for risk of musculoskeletal pain than found in our main models, and (2) among those with arthritis, statin use in the setting of 25(OH)D ≥15ng/mL was associated with significantly lower odds for risk of musculoskeletal pain. Regarding the second finding, other studies have reported similar observations regarding a possible protective effect of statin on reducing the risk or progression of arthritis [13,14]. However, vitamin D supplementation, on its own, was not found to improve symptoms or prevent progression of osteoarthritis [15].…”
Section: Discussionsupporting
confidence: 56%
“…The results from Clockaerts et al suggest that, compared with non-users, long-term statin users (Ͼ365 days) had reduced risks of radiographic knee OA (OR 0.49, 95% CI 0.26 -0.92) (8). Similarly, Chodick et al found that among statin * OR ϭ odds ratio; 99% CI ϭ 99% confidence interval; DDD ϭ cumulative defined daily dosage; NA ϭ not applicable; PF ϭ physical functioning subscale score.…”
Section: Peeters Et Almentioning
confidence: 99%
“…The DDD for each medication was defined according to the World Health Organization Anatomical Therapeutic Chemical/DDD index 2013 (18). The cumulative dose was categorized as Ͻ120, 120 -365, and Ն365 DDD, corresponding to 1 DDD per day for Ͻ4 months, 4 -12 months, and Ն12 months in agreement with categories used by Clockaerts et al (8).…”
Section: Participants the Australian Longitudinal Study Onmentioning
confidence: 99%
See 2 more Smart Citations